Excellent Madrasah Education: How do Learning Motivation and Al-Qur’an Literacy Synergize Tahfidzul Qur’an Acceleration? - Sri Bulan; M. Yunus Abu Bakar; Ah. Zakki Fuad (Southeast Asian Journal of Islamic Education, 2023)
To achieve the memorization target of 3 chapters of the Qur’an as a minimum requirement for graduation, MAN Insan Cendekia Pekalongan conducted a tahfidz quarantine program during Ramadan. This program focused on Al-Qur'an literacy activities as an effort to create student learning motivation in memorizing the Qur'an through the acceleration class model. This study aimed to determine the acceleration class model applied in the tahfidz quarantine and explore learning motivation and Al-Qur'an literacy. The research used a naturalistic qualitative descriptive method with a field case study approach which was conducted at MAN Insan Cendekia Pekalongan during the tahfidz quarantine. Data were obtained from interviews with the deputy head of the dormitory division, companion teachers, supervisor teachers, and students, as well as observation and documentation. From the total of 189 students, 14 student representatives from classes X and XI in each room were interviewed. Data analysis used Miles and Huberman's three steps including reduction, data display, and verification. The results showed that the memorization achievement of a minimum of 3 chapters was exceeded in the first and second weeks and there was an acceleration of memorization in the third and fourth weeks after the implementation of the acceleration class with the highest memorization achievement of 13 chapters for the male class and 19 chapters for the female class. The acceleration of memorization shows a significant increase due to the learning motivation and Al-Qur'an literacy which synergizes with the acceleration of tahfidzul Qur'an after the implementation of the acceleration classes.